Pengaruh intervensi psikoedukasi terhadap perilaku pencegahan stunting pada ibu baduta - Diana Br Sitepu; Evi Karota; Riswani Tanjung; Evawany Yunita Aritonang; Siti Zahara Nasution (Holistik Jurnal Kesehatan, 2026)
Background:  Stunting remains a major public health problem, particularly in developing countries, including Indonesia. This condition affects not only physical growth but also cognitive development and future productivity. Maternal behavior plays a crucial role in stunting prevention efforts, particularly during the first 1,000 days of life. Psychoeducation is one approach that can be used to improve stunting prevention behaviors through an interactive and participatory learning process. Purpose: To analyze the effect of psychoeducational interventions on stunting prevention behaviors in mothers of young children. Method: This study used a quasi-experimental design with a pretest-posttest control group approach. The study was conducted in the PB Selayang II Community Health Center in Medan. A total of 76 respondents were divided into two groups: 38 participants in the intervention group and 38 participants in the control group. Behavioral data were collected using a structured questionnaire and analyzed as a composite score. Because the data were not normally distributed, non-parametric tests, namely the Wilcoxon and Mann-Whitney tests, were used. Results: The median score for stunting prevention behavior in the intervention group increased from 86.39 in the pretest to 98.33 in the posttest. In contrast, the control group showed no significant change, from 85.97 to 85.28. The Wilcoxon test showed a significant difference in the intervention group (p < 0.001), while there was no significant difference in the control group (p = 0.421). Furthermore, the Mann–Whitney test showed a significant difference between the two groups (p < 0.001). Conclusion: The psychoeducational intervention significantly improved stunting prevention behavior in mothers of young children. This intervention has the potential to be a promotive and preventive strategy in primary health care.   Keywords: Children Under Two Years Old; Maternal Behavior; Primary Health Care; Psychoeducation; Stunting Prevention.